A New Technique For The Reconfiguration Of Radial Distribution Network For Loss Minimization - Shamsudin, Nur Hazahsha; Abidullah, Noor Athira; Abdullah, Abdul Rahim; Mamat, Mira Syuhadah; Sulaima, Mohamad Fani; Jaafar, Hazriq Izzuan (Engg Journals Publications, 2014)
-